Recurrence of cervical intraepithelial neoplasia in human immunodeficiency virus-infected women treated by means of electrosurgical excision of the transformation zone (LLETZ) in Rio de Janeiro, Brazil - Russomano, Fábio; Paz, Bruno Reis; Camargo, Maria José de; Grinsztejn, Beatriz; Friedman, Ruth Khalili; Tristao, Maria Aparecida Pereira; Oliveira, Caroline Alves (São Paulo Medical Journal, 2013)
CONTEXT AND OBJECTIVE: Human immunodeficiency virus (HIV)-infected women have higher incidence, prevalence, persistence and recurrence of pre-invasive cervical lesions (CIN II or III). The aim here was to investigate the risk of recurrence of CIN II/III among HIV-infected women (HIV+) and uninfected women in a cohort treated by means of large-loop excision of the transformation zone (LLETZ). DESIGN AND SETTING: Cohort study conducted at Instituto Fernandes Figueira/Fundação Oswaldo Cruz (IFF/Fiocruz). METHODS: 60 HIV+ and 209 HIV-negative patients were included in a cohort for follow-up after undergoing LLETZ to treat CIN II/III. A histopathological diagnosis of CIN II/III during the follow-up was taken to constitute recurrence. The following possible confounding variables were assessed: age at treatment and at end of follow-up; histological grade of intraepithelial disease treated; surgical margin involvement; adequacy of colposcopy during the follow-up; CD4+ lymphocyte count; HIV viral load; and type of antiretroviral therapy. RESULTS: Among the 60 HIV+ women, six showed recurrent disease during the follow-up. However, among the 209 HIV-negative women, seven showed a new precursor lesion. The relative risk of disease recurrence in the HIV+ women was 4.21 (95% CI = 1.42 to 12.43). The Kaplan-Meyer curve showed that the risk of recurrence was significantly higher among HIV+ women (log-rank test: P = 0.0111). CONCLUSION: The HIV+ women in our cohort presented a risk of CIN II/III recurrence at least 42% higher than among the HIV-negative women. These patients should form part of a rigorous screening and followup protocol for identification and appropriate treatment of cervical cancer precursor lesions.